2015
DOI: 10.3390/w7041402
|View full text |Cite
|
Sign up to set email alerts
|

Rainwater Harvesting for Small-Holder Horticulture in Namibia: Design of Garden Variants and Assessment of Climate Change Impacts and Adaptation

Abstract: Abstract:The design of rainwater harvesting based gardens requires considering current climate but also climate change during the lifespan of the facility. The goal of this study is to present an approach for designing garden variants that can be safely supplied with harvested rainwater, taking into account climate change and adaptation measures. In addition, the study presents a methodology to quantify the effects of climate change on rainwater harvesting based gardening. Results of the study may not be accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
0
15
1
Order By: Relevance
“…Several studies have explored the implementation of RWH systems in response to growing water demand in Africa [7,23,24], Asia [25][26][27], USA. [17][18][19][20][21][22][23][24][25][26][27][28] and Australia [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have explored the implementation of RWH systems in response to growing water demand in Africa [7,23,24], Asia [25][26][27], USA. [17][18][19][20][21][22][23][24][25][26][27][28] and Australia [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…From the respective of technical improvements, the impact factors on rainwater harvesting systems (RWH) include optimal tank size, technical design, and so on [1][2][3][4][5]. Technical improvements could effectively facilitate the operation of a new system, but they do not determine its successful operation.…”
Section: Introductionmentioning
confidence: 99%
“…Given the variability in rainfall, these designs should have allowed gardening with full storage capacity in approximately three out of four years. In-depth analysis of different gardening options using a tank flow model and an irrigation water model showed that even the negative impacts of climate change could be offset partly or completely by specific adaptation measures [58].…”
Section: Implementation Of the Research Processmentioning
confidence: 99%
“…All the mediating dimensions played their part in this achievement: the technological development of a variety of solutions for different conditions and forms of application [62,63], the establishment of ownership and governance structures [64], training and other instruments for capacity development such as the RFWH toolkit [65], studies on the impact of alternative gardening variants and the contribution to adapting to climate change [58]. A significant proportion of the references used were clearly non-academic, which is a typical and often underrated (societal) outcome of transdisciplinary research.…”
Section: Implementation Of the Research Processmentioning
confidence: 99%